The Question of Genre Classification in the Drama Series “Ubizo: The Calling (2007)” - Mjoli, Zingisa Noluvuyo (Centre for Film and Media Studies, 2023)
The paper argues that the South African television series, Ubizo: The Calling (d/Krijay Govender, 2007) blends elements of psychological thrillers, horrors as well as the gothic genre. The relationship of these subgenres is discussed in this paper in the context of the African spiritual practice of divine calling that is narrated by the series. The paper concludes that genre classification in this series is left unclear, whether it is horror or psychological thriller as suggested by its producers. For most parts of the series, horror conventions can be identified from the way the characters are set to the types of props and iconographies, as well as the set design and shot sizes of most scenes. Towards the end of the series, however, it changes focus thematically to fit a category that cannot be confined to one genre type. The effort of this research is to present concerns about the way in which some African spiritual practices are likened to sorcery due to the obsession with madness and ghosts. I used Indigenous Knowledge Systems together with genre analysis to arrive at my findings which were important in shedding light to the fact that some genres become less effective when they have been ideologically moved to other cultures. Upon on embarking on this research, I wanted to arrive at the certainty that western borrowed genres were bastardising African practices using foreign jargon and visuality to depict African spirituality. Indeed, the research was constructed in a manner that it simply wanted to confirm something that I, the author desperately wanted to believe. However, my own work has challenged me to acknowledge that these two can coexist.